Temporal Relationship between Serum Levels of Interleukin-6 and C-Reactive Protein in Therapeutic Hypothermia for Neonatal Hypoxic-Ischemic Encephalopathy - Saito, Junichi; Shibasaki, Jun; Shimokaze, Tomoyuki; Kishigami, Makoto; Ohyama, Makiko; Hoshino, Rikuo; Toyoshima, Katsuaki; Itani, Yasufumi (American Journal of Perinatology, 2016)
Objective C-reactive protein (CRP) is a useful marker of neonatal infection. Recent studies have shown that neonatal therapeutic hypothermia delays an elevation of CRP in infants with hypoxic-ischemic encephalopathy (HIE). This study investigated the time difference of peak levels of serum CRP and other inflammatory responses during therapeutic hypothermia.Study design We prospectively studied the serial serum data of CRP, interleukin-6 (IL-6), procalcitonin (PCT), and complete blood counts during the first week of life in HIE infants receiving therapeutic hypothermia.Results We identified 22 infants who received therapeutic hypothermia between August 2013 and July 2015. No infants developed clinically overt infections. The peak of serum levels of IL-6, PCT, and CRP were postnatal days 1, 2, and 4, respectively. White blood cells, neutrophils, and platelet counts gradually decreased from days 1 to 7. Early postnatal serum levels of IL-6 correlated with CRP on day 4 (IL-6 on day 2; r = 0.78, p < 0.001).Conclusion The peak value of CRP on day 4 might reflect the early production and secretion of IL-6 rather than an actual infection. Serial measurement of IL-6 might help avoid invasive sepsis workup and unnecessary change of antibiotics in infants.
Keywords: C-reactive protein; infants; interleukin-6; procalcitonin; sepsis